Hirondellea sindhusagar (Crustacea: Amphipoda: Lysianassoidea), a new deep-water scavenger species from the Indian Ocean, with a key to the genus Hirondellea - Horton, Tammy; Thurston, Michael (Zootaxa, 2009)
The amphipod genus Hirondellea Chevreux, 1889 is a cosmopolitan largely bathyal genus. This paper adds a new species from the bathyal Arabian Sea, Indian Ocean, based on material collected by baited traps at 1182, 1184 and 1864 m off the coast of Pakistan. The species can be distinguished from the most closely allied species, Hirondellea brevicaudata (Chevreux, 1910) by the subacute lateral head lobes, the very weakly cleft telson, and characters of the mouthparts. A key to the ten species in the genus is provided.